Реформація як чинник європейської історії Нового часу (до 500-річчя Реформації в Європі) - Крамар, Ю. В.; Kramar, Yurii (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлюється місце та роль Реформації в європейській історії XVI-XVII ст. Проаналізовано чинники, які сприяли появі реформаційного руху в Європі. Охарактеризовано основні течії протестантизму. Показано місце Реформації у формуванні цінностей західноєвропейської цивілізації.In this article a place and a role of the Reformation in the European history of XVI- XVII centuries are illuminated. It is found out that the Reformation became one of the main stages in the development of European civilization. The factors which assisted to the appearance of reformed movement in Europe were analysed. The origin of the Reformation was connected with the general crises of medieval society and its institutions, in particular, church. Among the main preconditions of the Reformation were forming of new social estate - bourgeoisie and changing of the intellectual community in Europe which were caused by spreading the ideas of humanism in the period of the Renaissance.
The Reformation as a Factor of New Time in the European History (to the 500th Anniversary of the Reformation in Europe)
Keywords: Реформація; держава; церква; релігія; протестантизм; М. Лютер; Ж. Кальвін; the Reformation; state; church; religion; protestantism; М. Luter; G. Calvin